Monitoring and maintaining groundwater quality: challenges and management - Zhu hang, Goh; Maelissa, Nelda; Zhang Zhan, Loh; Widiyanti, Atik; Umarie, Winda; Setiadi Soedjono, Eddy (Universitas Nahdlatul Ulama Surabaya, 2022)
Water covers 70% of the world’s total surface, but only around 3% of it is freshwater that humans may drink and utilize for other purposes. Because of fast growth in many nations, the quality of groundwater is no longer adequate for human consumption. The objective of the study is to assess the groundwater quality of 18 locations in the Ropar wetland in Punjab, India, in different seasons and different source groundwater. When compared to uncontaminated natural groundwater, the groundwater obtained from the test sites had higher pH values. The amount of groundwater pollution is higher in the summer than in the winter. However, there are many challenges face by the groundwater quality research. The groundwater quality in any region of the world is very important towards the survival of human being. Long-term consumption of polluted groundwater with high levels of heavy metals will result in health issues such as difficulty breathing and renal failure.